2017
DOI: 10.1111/jvh.12821
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA expression profiles in HBV‐transformed human hepatocellular carcinoma cells treated with a novel inhibitor of human La protein

Abstract: Summary We previously identified a novel inhibitor of La protein, H11, which inhibited hepatitis B virus (HBV) replication by inhibiting the interaction between La protein and HBV RNA. However, the other cellular factors involved in this process remain unclear. To investigate the mechanism of H11‐mediated inhibition of HBV infection, a lncRNA microarray analysis was performed using H11‐treated and untreated stable HBV‐expressing human hepatoblastoma HepG2.2.15 cells. The profiles of differentially expressed ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, many research studies indicated that lncRNAs might mediate the expression of neighboring and distantly located genes via cis/trans regulatory effects, respectively, and the genomic context could, therefore, provide important information about the potential functions of lncRNAs 7,20 . Therefore, most researchers always indirectly predict the functions of lncRNAs by performing GO and pathway analysis of their neighboring and distantly target genes 21,22 . However, to investigate the integrated functions of lncRNAs, we performed GSEA base on Pearson's correlation coefficient between the selected lncRNA and all mRNAs in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many research studies indicated that lncRNAs might mediate the expression of neighboring and distantly located genes via cis/trans regulatory effects, respectively, and the genomic context could, therefore, provide important information about the potential functions of lncRNAs 7,20 . Therefore, most researchers always indirectly predict the functions of lncRNAs by performing GO and pathway analysis of their neighboring and distantly target genes 21,22 . However, to investigate the integrated functions of lncRNAs, we performed GSEA base on Pearson's correlation coefficient between the selected lncRNA and all mRNAs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…7,20 Therefore, most researchers always indirectly predict the functions of lncRNAs by performing GO and pathway analysis of their neighboring and distantly target genes. 21,22 However, to investigate the integrated functions of lncRNAs, we performed GSEA base on Pearson's correlation coefficient between the selected lncRNA and all mRNAs in this study. Largely consistent with the results of enrichment analysis of the differentially expressed mRNAs, the top 10 upregulated and 10 downregulated lncRNAs were also primarily involved in the biotransformation process, such as fatty acid metabolism, amino acid metabolism, carbon metabolism, and drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we used microarray and quantitative real‐time PCR to investigate the mechanism of H11‐mediated inhibition of HBV infection. The results showed that HBSC11‐induced inhibition of HBV replication was mediated via miR‐ 3912‐5p, miR‐6793‐5p, and miR‐7159‐5p and participation in the Wnt, beta‐catenin, and PPAR signaling pathways . Further research is underway on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Many lncRNAs are reportedly dysregulated in HBV-related HCC and HBV/HBx expressing cells. 80,81 Most of the studies only focused on the dysregulation of lncRNA and a few of these have actually focused on the molecular mechanism. In HBV related HCC, two autophagy-related lncRNAs, HOTAIR and HULC were studied in detail.…”
Section: Hbv and Autophagymentioning
confidence: 99%